Effects of oxidation degree of support and phosphorus modification on the catalytic cracking of coal pyrolysis tar by char-supported nickel catalysts. (April 2023) - Zhang, Xufeng; Yan, Lunjing; Niu, Huifang; Wang, Meijun; Kong, Jiao; Bao, Weiren; Chang, Liping
Abstract: The low rank coal can be converted efficiently when it undergoes the pyrolysis process. The utilization of tar is modified and the problems such as pipeline blockage are solved by cracking and lightning heavy components in tar. In this study, the char-supported nickel (Ni) catalysts were prepared by different Ni loading methods, and the cracking of coal pyrolysis tar was improved by the coal char support with different oxidation degrees. The catalysts prepared by ion exchange method showed better performance for the tar cracking than other methods, which is related to their smaller Ni crystallite size (NCS). The oxidation of H2 O2 and HNO3 significantly increased the number of oxygen-containing groups. The intrinsic correlation between oxidation degree of support and catalytic property indicated that the XH2 O2 -Ni/C (ZD coal pretreated by H2 O2 ) series catalysts had better tar cracking activity than XHNO3 -Ni/C (ZD coal pretreated by HNO3 ) series catalysts, which did not only depend on the increase of Ni loading amounts but also related to the smaller NCS and higher dispersion. Moreover, the non-metallic additive phosphorus (P) was added to modify the catalysts. It was found that the addition of P significantly improved the tar cracking performance of the 30%H2 O2 P-Ni/C catalyst. The amounts of active components loaded and NCS contributed to the production of light tar. Highlights: Char-supported Ni catalysts were prepared by different Ni loading methods. The catalyst prepared by ion exchange method showed considerable performance. The oxidation of support by H2 O2  and HNO3 can change the Ni loading and Ni crystallite size. P modification can significantly affect the distribution of active components and promote catalytic performance.